2022
DOI: 10.3390/ijms23137343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Gentamicin and Furosemide Treatment on Cochlear Macrophages

Abstract: Combining aminoglycosides and loop diuretics often serves as an effective ototoxic approach to deafen experimental animals. The treatment results in rapid hair cell loss with extended macrophage presence in the cochlea, creating a sterile inflammatory environment. Although the early recruitment of macrophages is typically neuroprotective, the delay in the resolution of macrophage activity can be a complication if the damaged cochlea is used as a model to study subsequent therapeutic strategies. Here, we applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Recently, human studies showed the manifestation of the production of fractalkine gene transcripts in SGNs, spiral lamina regions, and basilar membrane ( 4 ). Macrophage function may depend on the location and differences in macrophage morphology and distribution between the apical and basal regions of the cochlea have been described ( 18 ). It could explain the different vulnerability of the sensory nerves and receptors in the cochlea ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, human studies showed the manifestation of the production of fractalkine gene transcripts in SGNs, spiral lamina regions, and basilar membrane ( 4 ). Macrophage function may depend on the location and differences in macrophage morphology and distribution between the apical and basal regions of the cochlea have been described ( 18 ). It could explain the different vulnerability of the sensory nerves and receptors in the cochlea ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%